2014
DOI: 10.1016/j.actamat.2014.02.043
|View full text |Cite
|
Sign up to set email alerts
|

Tensile elongation of unidirectional or laminated composites combining a brittle reinforcement with a ductile strain and strain-rate hardening matrix

Abstract: We use the long-wavelength model of Hutchinson and Neale (Hutchinson JW, Neale KW. Acta Metall 1977;25:839) and Ghosh (Ghosh AK. Acta Metall 1977;25:1413) to estimate the uniform tensile elongation of two-phase composites deforming quasistatically according to the equistrain rule of mixtures, in which one phase is ductile while the other fractures progressively according to twoparameter Weibull statistics. We use shear-lag models in the literature to quantify load transfer from the ductile phase to the frac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 55 publications
0
6
0
Order By: Relevance
“…The fracture elongation of multilayer metal matrix composites should be located in the intermediate value of the constitute metals if neglected of m value. However, the actual tensile ductility of laminated metal matrix composites is always lower or higher than the constitute metals [61,62]. That is to say, the fracture elongation of multilayer metal matrix composites heavily depends on the strain rate sensitivity factor (m).…”
Section: Superplastic Deformation Behaviormentioning
confidence: 99%
See 1 more Smart Citation
“…The fracture elongation of multilayer metal matrix composites should be located in the intermediate value of the constitute metals if neglected of m value. However, the actual tensile ductility of laminated metal matrix composites is always lower or higher than the constitute metals [61,62]. That is to say, the fracture elongation of multilayer metal matrix composites heavily depends on the strain rate sensitivity factor (m).…”
Section: Superplastic Deformation Behaviormentioning
confidence: 99%
“…ε r is the reference strain rate, high strain hardening exponent (n) represents high uniform plastic deformation capacity, and high strain rate sensitivity factor (m) reveals superior tensile deformation behavior [61,62]. The m value does not delay localized necking, but also retains a series of diffuse necking.…”
Section: Superplastic Deformation Behaviormentioning
confidence: 99%
“…The laminated composites with superior tensile ductility can be obtained by adjusting the values of n and m of constitute layer [80]. Figure 18 shows the fracture elongation map of many power-law hardening monolithic materials [80,81]. It is interesting to note that a low ductility material laminated with another material that can coax the laminated composites toward higher elongation.…”
Section: Strain Hardening Exponent (N) and Strain Rate Parameter (M)mentioning
confidence: 99%
“…In addition, compared with syntactic Al and high strength alloy foams, the existing metallic glass foams have no significant advantage in energy absorption [18][19][20][21][22]. Fortunately, it is shown that the addition of non-metallic such as brittle ceramic particles and fibers is an effective way to produce materials with attractive engineering attributes [23][24][25][26]. The high content of brittle second phases can increase both the strength and ductility of composites [25,26].…”
mentioning
confidence: 99%
“…Fortunately, it is shown that the addition of non-metallic such as brittle ceramic particles and fibers is an effective way to produce materials with attractive engineering attributes [23][24][25][26]. The high content of brittle second phases can increase both the strength and ductility of composites [25,26]. In this paper, using hollow ceramic microspheres as a reinforcer that are also effective in avoiding crystallization, we fabricate a BMG syntactic foam through pressure infiltration, which was previously applied to make metal matrix composites with monolithic (non-hollow) ceramic reinforcement [27].…”
mentioning
confidence: 99%